2022
DOI: 10.37817/ikraith-ekonomika.v5i3.2460
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tingkat Pendidikan, Upah Minimum, Dan PDRB Terhadap Penyerapan Tenaga Kerja Di Kabupate/Kota Provinsi Jawa Barat

Abstract: Provinsi Jawa Barat menjadi sentra ekonomi yang memiliki banyak jumlah penduduk usia produktifdi Indonesia yang akan menghadapi masa bonus demografi. Tingginya tingkat pengangguran di daerahtersebut menjadi permasalahan ketenagakerjaan yang mengindikasikan bahwa penyerapan tenagakerja belum optimal dengan beberapa faktor yang dapat mempengaruhinya. Tujuan penelitian ini yaituuntuk mengetahui pengaruh variabel tingkat pendidikan, upah minimum, dan PDRB secara parsial dansimultan terhadap penyerapan tenaga kerja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Economic growth comes from three factors, namely quality, quantity and increase in workforce so that companies recruit more workers from outside the region with high quality education. Research by Rahmah & Juliannisa, (2022)strengthens the results of research that GRDP has no effect on labor absorption because if economic growth increases but does not coincide with an increase in employment opportunities, not only that, this condition can also occur if economic growth decreases so it will have an impact on labor absorption.…”
Section: The Impact Of Economic Growth On Workforce Absorptionmentioning
confidence: 89%
See 1 more Smart Citation
“…Economic growth comes from three factors, namely quality, quantity and increase in workforce so that companies recruit more workers from outside the region with high quality education. Research by Rahmah & Juliannisa, (2022)strengthens the results of research that GRDP has no effect on labor absorption because if economic growth increases but does not coincide with an increase in employment opportunities, not only that, this condition can also occur if economic growth decreases so it will have an impact on labor absorption.…”
Section: The Impact Of Economic Growth On Workforce Absorptionmentioning
confidence: 89%
“…This outcome is consistent with the research by Atiyatna et al,(2016) which asserts that minimum wage, economic growth, and education collectively influence workforce absorption in South Sumatra Province. Another research by Rahmah & Juliannisa, (2022) found that education level, minimum wage, and Gross Regional Domestic Product (PDRB) collectively influence workforce absorption in West Java Province.…”
Section: The Impact Of Economic Growth On Workforce Absorptionmentioning
confidence: 99%
“…Menurut teori human capital oleh Becker dalam (Rahmah & Juliannisa, 2020) menjelaskan produktivitas tenaga kerja bersumber dari adanya keterampilan yang dimiliki oleh pekerja, sehingga bisa meningkatkan produk marjinal pekerja tersebut. Para pekerja harus melalui proses pendidikan untuk memiliki keterampilan tersebut, sehingga sumber daya manusia membutuhkan pendidikan.…”
Section: Kajian Teoritisunclassified
“…Education shows human capital in skills, knowledge, independence, and the formation of one's personality. According to Rahmah & Juliannisa (2022), expertise is an important capital for the workforce in achieving productivity. The type of education influences a person in choosing a particular job.…”
Section: Literature Reviewmentioning
confidence: 99%